CONTROL OF THE SKILLS AND ABILITIES OF THE STUDENTS - Dadahonova , Zulaykho (Innovative Development in Educational Activities, 2023)
The article describes the importance and actuality of control in the lessons of foreign languages nowadays. It also classifies and explains control functions, types, forms and its means.